Making the incommensurable comparable: a comparative approach to pluralist economics education - Andreas Dimmelmeier; Frederick Heussner; Andrea Pürckhauer; Janina Urban (European Journal of Economics and Economic Policies: Intervention (EJEEP), 2017)
Demands for pluralism in economics education have been widespread in recent years. As change in the universities is slow and piecemeal, we present a comparative approach to economics which builds the intellectual basis for the online learning platform Exploring Economics (www.exploring-economics.org). This approach is committed to a vision of theoretical and methodological pluralism and is grounded in concepts derived from biology, the history of economic thought, the philosophy of science and international political economy. We find central categories in which the ten schools of economic thought selected show meta-theoretical patterns which may not only serve as a guide to economics education but may also be relevant for economics research.
Keywords: A2; B4; B5; Z13; 330; economics education; teaching of economics; pluralist economics; philosophy of economics; taxonomy; meta-analysis